Analyzing Foregone Cash to Improve Utility Performance - Balabanyan, Ani; Hankinson, Denzel; Nash, Stephen; Singh, Arun (World Bank, Washington, DC, 2021)
The level of performance of an electric utility is determined by the soundness of its financial situation, the efficiency of its technology, and the quality of service it provides customers. Its financial underpinning is a balance of costs and revenue (from customer payments, government, and other sources). But revenue is not as straightforward as it might seem. The concept of foregone cash addresses the ‘cash on the table’ that pays for operations and servicing debt (revenue collected divided by the cost of operations and debt). The problem is the table may not have all the cash that ought to be there, such as money owed because of nonpayment’s by customers and money lost through inefficiencies in power generation or delivery. Consequently, there is a latent revenue that, if fixed, can provide vital improvements to a utility’s financial performance. This note analyzes the elements involved in understanding foregone cash in the context of cost recovery.